Estrategias para reducir la rotación de personal en el contexto laboral colombiano (2021)
Staff turnover has been integrated into the Colombian industry as part of the management of human talent, impossible to be avoided in its entirety, generating unnecessary costs and expenditure of resources. In this research, a bibliographic and theoretical review will be carried out on the phenomenon of staff turnover in Colombian private sector companies during the fourth industrial revolution and the importance of the implementation of strategies that seek to minimize its effect. With the information collected and in light of the analysis of different strategies applied by Colombian companies during the health crisis of 2020, recommendations will be made in the abstract, adaptable to different business sectors in Colombia, so that staff turnover is reduced to its minimum expression.